2021
DOI: 10.3390/challe12020020
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Lockdown Policies and Their Effectiveness in Romania and Hungary

Abstract: There has been a debate on the efficiency of lockdown policies worldwide, and several researchers have studied this aspect by trying to implement different statistical models. The aim of the research was to compare two countries with similar lockdown policies and observe the impact of the total lockdown policy on the spread of the COVID-19 disease. Taking in consideration that the total lockdown in Romania lasted for 52 days and in Hungary for 54 days, we would like to see how the infection rate changed with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, lonely people experienced significantly less time with loved ones [z (1,756) = −2.5, p = 0.012] and less sense of togetherness [z (1,756) = −2.39, p = 0.017] than non-lonely people. There was no significant difference between lonely and non-lonely individuals in experiencing a more "eco-friendly world" [z (1,756) = −0.009, p = 0.99], "more time to think about life" [z (1,756) = 1.12, p = 0.295], "more time for hobbies" [z (…”
Section: Less Positive Experiences Of Living In Covid-among Lonely In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, lonely people experienced significantly less time with loved ones [z (1,756) = −2.5, p = 0.012] and less sense of togetherness [z (1,756) = −2.39, p = 0.017] than non-lonely people. There was no significant difference between lonely and non-lonely individuals in experiencing a more "eco-friendly world" [z (1,756) = −0.009, p = 0.99], "more time to think about life" [z (1,756) = 1.12, p = 0.295], "more time for hobbies" [z (…”
Section: Less Positive Experiences Of Living In Covid-among Lonely In...mentioning
confidence: 99%
“…With the start of lockdown during the beginning of COVID-19, it was uncertain how long the significant changes that governments made would last. Those changes brought grand challenges to life, such as preventing the virus from spreading around the world (e.g., wearing a mask) (1), staying at home to protect children and vulnerable adults (2)(3)(4), and staying connected when physically apart (5)(6)(7). The World Health Organization reported that the global prevalence of anxiety and depression increased by a massive 25% in the first year of COVID-19 (8).…”
Section: Introductionmentioning
confidence: 99%
“…Lockdowns of varying intensity, sometimes referred to as “stay at home” orders in their strictest manifestation, have been among the first remedies adopted by governments, and literature dealing with the efficacy of NPIs has therefore concentrated on them as a priority. Most contributions have suggested that lockdown measures effectively reduce the spread of the virus (among others, Alfano and Ercolano, 2020a ; Figueireido et al, 2020; Imai et al, 2020 ; Lau et al, 2020 ; Kerekes et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ambivalent response to these is probably due to the considerable economic cost that the enforcement of such policies implies. 2 Although this literature is very recent, due to the on-going nature of the emergency, a number of scholars have already investigated the efficacy of NPIs, both in terms of control of the spread of the virus, 2,3,4,5,6,7,8,9,10 and of the determinants of their effectiveness. 11,12,13 Together with closures of economic and social activities, public events were deleted or postponed.…”
Section: Introductionmentioning
confidence: 99%